Outcomes of Hepatitis E in Pregnancy - Iram Inam, Ghias ul Hassan, Saboohi Saeed, Saadia Sajjad, Saima Sheikh (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Hepatitis E virus infection is an emerging challenge of the developing world. During pregnancy, hepatitis E Virus results in devastating effects endangering the life of both mother and fetus. Hepatitis E contribute to 19% to 25% of maternal and 7-13% of all neonatal deaths. Purpose of this study is to see the association between hepatitis E virus infection and feto-maternal outcomes in pregnancy. Material & Methods: A prospective study design was used. Study was conducted in a tertiary health care sector for a period of March 2018 to January 2021 with sample size of 60 pregnant women. Study was conducted after getting institutional approval and informed consent was taken from all the study participants. Ethical considerations were followed throughout the study period. Data was analyzed using SPSS version 23.0 and descriptive statistics was used. Results: Out of 60 pregnancies, 19 (30%) suffered with PPH, 14 (23.33%) had history of DIC and 16 (26.66%) cases of hepatic encephalopathy were evident. Preterm SVD was a majority reason seen for ending the pregnancy. Results showed that hepatitis E virus caused multiple fetal morbidities. Conclusion: High mortality rate was evident in hepatitis E virus infection affected pregnancies in this study. There is a need to educate pregnant ladies regarding preventive measures to avoid fulminant consequences. Emphasis should be given to follow hygienic practices during pregnancy and proper antenatal visits are mandatory to educate the women.